Effect of number of branches on the performance of fractal impeller in a stirred tank: mixing and hydrodynamics - Mule, Gunwant M.; Lohia, Rajat; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2016)
Number of blades of an impeller, impeller design and its positioning in a stirred tank is known to affect the mixing in a stirred tank reactor. The extent of non-uniformity in mixing from conventional impellers can be reduced significantly using a space-filling impeller like a fractal impeller. In this work, we report the effect of number of branches (and hence the number of blades) of fractal impeller on power consumption, mixing and hydrodynamics. Velocity measurements were carried out using ultrasonic velocity profiler (UVP). Measurements showed that the performance of fractal impeller with different configuration is equivalent, however, better than standard impellers in terms of mixing achieved per unit power consumption. No significant difference was observed in radial and axial mean velocity profiles for three different configurations. However, the tangential velocity was found higher for four branches than two and three branches FL Two distinct circulation loops were observed in upper as well as lower half of the vessel in r-z plane. Strong tangential flow throughout the baffled vessel helps to achieve good mixing even at low rotational speeds. (C) 2016 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Fractal impeller; Number of branches; UVP; Tangential velocity; Mixing